Design of millimeter-wave chipless tag based on variable angle arc resonator. Issue 1 (June 2021) - Zhang, Qianglin; Zou, Chuanyun; Jiao, Liangyu
Abstract: Faced with the development of miniaturization and compactness of chipless radio frequency identification (RFID) tags, and to reduce the cost of traditional chip tags, this paper proposes a miniaturized, polarization-insensitive, passive, and chipless based on a variable-angle arc resonator. Chipless tags have a high coding density of 44.44 bits/cm 2 in the frequency range of 20GHz∼31GHz, and a coding capacity of 4.04 bits/cm 2 /GHz. The patch on the substrate determines the signature of each resonant frequency, thereby determining the number of identification data bits. To accommodate more data bits and pass barriers between resonant features, the metal patches are orthogonally polarized so that adjacent resonant features will not interfere with each other. As the mm-Waves ultra-wideband (UWB) chipless tags, it can be easily printed on various IoT applications and has great potential for low cost and identity verification. This work makes it easier to implement highly robust, inexpensive, and flexible chipless tags for IoT applications in the mm-Wave band.